2022
DOI: 10.1002/ana.26298
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Phenoconversion in Rapid Eye Movement Sleep Behavior Disorder

Abstract: Objective This study was undertaken to follow up predictive factors for α‐synuclein–related neurodegenerative diseases in a multicenter cohort of idiopathic/isolated rapid eye movement sleep behavior disorder (iRBD). Methods Patients with iRBD from 12 centers underwent a detailed assessment for potential environmental and lifestyle risk factors via a standardized questionnaire at baseline. Patients were then prospectively followed and received assessments for parkinsonism or dementia during follow‐up. The cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 43 publications
4
42
0
Order By: Relevance
“…A rather unexpected finding of the association of DEB with younger age is in contrast to the finding that increasing age is a risk factor for RBD (Zhang et al, 2022 ). In other words, there will be a distinct possibility that this young age group may suffer from DEB‐like episodes related to non‐REM (NREM) parasomnia during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 85%
“…A rather unexpected finding of the association of DEB with younger age is in contrast to the finding that increasing age is a risk factor for RBD (Zhang et al, 2022 ). In other words, there will be a distinct possibility that this young age group may suffer from DEB‐like episodes related to non‐REM (NREM) parasomnia during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 85%
“…The so-called symptomatic RBD, on the other hand, occurs in association with neurodegenerative diseases belonging to the α-synucleinopathies, narcolepsy, and subacute-or acute-onset conditions involving the central nervous system (structural brain lesions, CNS diseases, drug consumption or alcohol withdrawal, and post-traumatic stress disorder) [1]. In recent years, follow-up studies have shown that most iRBD patients will develop an overt alphasynucleinopathy over time, with a rate of phenoconversion of 73.5% after 12 years from diagnosis [10][11][12][13]. RBD thus represents an early marker of neurodegeneration, a unique open window on the initial phase of alpha-synucleinopathies, encouraging research on neuroprotective therapies [14].…”
Section: Introductionmentioning
confidence: 99%
“…The explanation for this result may be that openness trait might be affected by other variables in iRBD. Previous studies suggested that older age and poor cognition could predict future phenoconversion in iRBD patients, which are also tightly related to open personality trait [15][16][17][18] . Thus, age and cognition might modulate the effect of openness on future phenoconversion.…”
Section: Discussionmentioning
confidence: 99%